2020
DOI: 10.1136/jitc-2019-000416
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of human cancer xenografts in humanized mice

Abstract: BackgroundPreclinical evaluation of drugs targeting the human immune system has posed challenges for oncology researchers. Since the commercial introduction of humanized mice, antitumor efficacy and pharmacodynamic studies can now be performed with human cancer cells within mice bearing components of a human immune system. However, development and characterization of these models is necessary to understand which model may be best suited for different agents.MethodsWe characterized A375, A549, Caki-1, H1299, H1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
55
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(62 citation statements)
references
References 22 publications
7
55
0
Order By: Relevance
“…The majority of the non-T cells in tumors of our HIS-BRGS mice was of the myeloid lineage ( 23 ). Altogether, and consistent with other studies in HIS-mice ( 44 , 84 ), these data suggest the tumors in our HIS-BRGS model generally recapitulate their unique TME in regard to immune infiltration.…”
Section: Resultssupporting
confidence: 92%
See 2 more Smart Citations
“…The majority of the non-T cells in tumors of our HIS-BRGS mice was of the myeloid lineage ( 23 ). Altogether, and consistent with other studies in HIS-mice ( 44 , 84 ), these data suggest the tumors in our HIS-BRGS model generally recapitulate their unique TME in regard to immune infiltration.…”
Section: Resultssupporting
confidence: 92%
“…In summary, we provide ample evidence that human xenografts grow in the multi-lineage HIS models generated from human HSCs. As similarly observed by other groups ( 50 , 84 ), we achieved high and reproducible tumor take rates in our HIS-BRGS mice.…”
Section: Resultssupporting
confidence: 89%
See 1 more Smart Citation
“…FOXP3 stained cells, presumed to be regulatory T cells were significantly decreased by a third compared to vehicle control. Rios-Doria et al characterized several xenograft models using humanized mice and revealed that the antitumor response of the models to immunotherapy was positively associated with the induced levels of CD4 and CD8 tumor-infiltrating lymphocytes ( Rios-Doria et al, 2020 ). Moreover, CD8 T cells were essential for the antitumor immune response of the murine IFN-β-immunocytokine ( Yang et al, 2014 ).…”
Section: Discussionmentioning
confidence: 99%
“…The HU-CD34 model has been successfully combined with several cell line-derived xenografts and PDXs of different cancer types (137)(138)(139). Although a perfect HLA match between CD34+ HSC donor and tumor patient is impossible, a partial HLA match did not negatively affect tumor growth in recent reports on PDXs (139,140).…”
Section: Hu-cd34 Modelmentioning
confidence: 99%